ANALISIS PENGARUH RELIGIUSITAS, TINGKAT PENDAPATAN, KUALITAS PELAYANAN DAN TINGKAT KEPERCAYAAN TERHADAP MINAT MEMBAYAR ZAKAT (Studi Kasus pada Lazismu Kota Pekalongan) - Solikhah, Faridatus; Purwanto, Teguh; Arifiyanto, Muhammad; Rizaldi, Herna; Moegiri, Moegiri (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2023)
This study aimed to analyzed the effect of religiosity, income level, quality of services andtrust on obedience in paying zakat. Data were gathered through distributing questionnaires. The study applied purposive sampling method with the slovin formula. There are 94 respondents who ware muzakki who were registered at the Muhammadiyah Amil Zakat, Infaq and Alms Organization (LAZISMU) Pekalongan City. Thedate were analyzed using multiple linierregression using SPSS 16. Partially, the results show that religiosity, income level, services quality and level oftrust have a signifikcant effecton obedience in paying zakat. Then simultaneously that religiosity, income level, services qualityand level of trust together have a significant effect on onedience in paying zakat. REFERENSI Ahmadi, A. (2004). Psikologis Umum. Jakarta: Rinika Cipta Al-Farizi. Amir, M. T. (2005). Dinamika Pemasaran. Jakarta: Grafindo Persada. Augusty, F. (2006). Metode Penelitian Manajemen: Pedoman Penelitian untuk Skripsi, Tesis dan sisrtai Ilmu Manajemen. Semarang: Universitas Diponegoro. Fandy, T. (2014). Kualitas Jasa. Jakarta: Andi Offset. Ghozaly, I. (2011). Aplikasi Analisis Multivariate dengan Program IBM SPSS 19. Semarang: Universitas Diponegoro. Ghozaly, I. (2013). Aplikasi Analisis Multivariate dengan Program IBM SPSS 19 . Semarang: Universitas Diponegoro. Muhammad. (2008). Zakat Profesi: Wacana Pemikiran dan Fiqih Kontemporer . Jakarta: Salemba Diniyah. Primadana, D. (2018). Pengaruh Religiusitas , Tingkat Pendapatan, Layanan Terhadap Minat Membayar Zakat Pada Lembaga Amil Zakat Rizki Jember . Jember: Unveritas Jember. Rahmat, J. (2003). Psikologis Agama. Bandung: PT.Mizan Pustaka. Sadono, S. (1995). Pengantar Makro Ekonomi . Jakarta: Grafindo Persada. Kholidah, N., & Salma, A. N. (2019). Filantropi kreatif: Pemberdayaan ekonomi umat berbasis zakat produktif pada program 1000 UMKM LAZISMU Kabupaten Pekalongan. Cakrawala: Jurnal Studi Islam, 14(2), 93-101. Susanti, L., & Triatmaja, M. F. (2023). Pengaruh Religiusitas Dan Green Consciousness Terhadap Keputusan Pembelian Sabun Cuci Green Wash. Media Ekonomi, 23(1), 1-12. Kholidah, N., Hakim, M. R., & Purwanto, E. (2019). Analisis Kinerja Reksadana Saham Syariah Dengan Metode Sharpe, Treynor, Jensen, M², dan TT. Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 1(2), 29-40. Arifiyanto, M., & Kholidah, N. (2021). Analisis pengaruh pengetahuan produk, persepsi manfaat dan promosi terhadap minat penggunaan uang elektronik berbasis server. JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 7(3). Hakim, M. R., Kholidah, N., & Arifiyanto, M. (2022). Factors Affecting Muzakki's Decision In Choosing to Pay Zakat At Amil Zakat Institution. Robust: Research of Business and Economics Studies, 1(2), 57-73.